Studies on the density, distribution, and surface phenotype of intraepithelial class II major histocompatibility complex antigen (Ia)- bearing dendritic cells (DC) in the conducting airways (The Rockefeller University Press, 1991)
Conventional immunohistochemical analysis of airway intraepithelial class II major histocompatibility complex (Ia) expression demonstrates a morphologically heterogeneous pattern of staining, suggestive of the presence of a mixed population of endogenous antigen presenting cells. Employing a novel tissue sectioning technique in conjunction with optimal surface antigen fixation, we now demonstrate that virtually all intraepithelial Ia staining throughout the respiratory tree in the normal rat, can be accounted for by a network of cells with classical dendritic cell (DC) morphology. The density of DC varies from 600-800 per mm2 epithelial surface in the large airways, to 75 per mm2 in the epithelium of the small airways of the peripheral lung. All the airway DC costain for CD4, with low-moderate expression of a variety of other leukocyte surface markers. Both chronic (eosinophilic) inflammation and acute (neutrophilic) inflammation, caused respectively by inhalation of chemical irritants in dust or aerosolised bacterial lipopolysaccharide (LPS), are shown to be accompanied by increased intraepithelial DC density in the large airways (in the order of 50%) and up to threefold increased expression of activation markers, including the beta chain of CD11/18. The kinetics of the changes in the DC network in response to LPS mirrored those of the transient neutrophil influx, suggesting that airway intraepithelial DC constitute a dynamic population which is rapidly upregulated in response to local inflammation. These findings have important theoretical implications for research on T cell activation in the context of allergic and infectious diseases in the respiratory tract.